Factors Associated with the Occurrence of 0PN Fertilization in in Vitro Fertilization and its Effects on Embryo Development and Reproductive Outcomes - Hongmin Guo; Xinhui Sun; Yueyue Jia; Jing Du (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: To investigate factors associated with the occurrence of nonpronuclear (0PN) fertilization and to determine its effects on embryo development and reproductive outcomes in conventional in vitro fertilization (cIVF). Methods: This retrospective cohort study included 1116 IVF cycles and the corresponding 535 fresh transfer cycles performed during 2016–2022. Patients were divided into 0PN (+) (n = 279) and 0PN (–) (n = 837) groups based on whether they had embryos with 0PN fertilization. A multiple logistic regression model was used to determine confounders that could affect 0PN fertilization. Additionally, embryo development and reproductive outcomes were compared between the 0PN (+) and 0PN (–) groups, as well as between the 0PN embryo (n = 563) and two pronuclear (2PN) embryo (n = 1976) groups. Results: The number of mature oocytes was significantly correlated with the occurrence of 0PN fertilization (odds ratio: 1.15; 95% confidence interval 1.04–1.27; p = 0.007). The top-quality embryo rate was significantly higher in the 0PN (+) group than in the 0PN (–) group (52.9% vs. 49.9%; p = 0.024). Clinical outcomes were similar between these groups in terms of clinical pregnancy rates (43.1% vs. 45.5%), implantation rates (35.0% vs. 34.1%), miscarriage rates (15.3% vs. 17.1%), and live birth rates (33.6% vs. 33.9%). The top-quality embryo rates (45.3% vs. 52.9%, p = 0.001) and blastulation rates (57.7% vs. 63.8%, p = 0.023) were significantly lower in 0PN embryos than in 2PN embryos. The clinical outcomes were also similar between these groups. Conclusions: The number of mature oocytes is significantly correlated with the occurrence of 0PN fertilization in cIVF. 0PN fertilization does not affect reproductive outcomes during fresh transfer cycles.